Multicultural Islamic Education Values at Vocational Secondary School - Burhanuddin, Hamam; Sahri; Nafi, Ahmad (LETIGES, 2025)
This study aims to examine the instillation of Islamic Multicultural Education values ​​at SMK Negeri Jatirogo Tuban which contains multicultural values. This type of research is a field study with a qualitative approach. Sources of information regarding this study are Islamic and Christian Religious Education Teachers, Principals or Assistant Teachers, and Students. Data collection techniques are carried out through interviews, participant observation, and documentation. Data analysis techniques are carried out using data collection techniques, data reduction, data presentation and data inference. The findings in this study indicate that the multicultural values ​​contained in Islamic education include tolerance values, equality values, unity values, family values, and justice values. The implementation of multicultural values ​​in Islamic Religious Education learning at SMK Negeri Jatirogo Tuban uses two methods, namely the exemplary method and the habitat method. The impact of instilling multicultural values ​​on students is the growth of attitudes of mutual tolerance, respect, accepting other people's opinions, mutual cooperation, not being hostile and the absence of conflict due to differences in culture, ethnicity, language, customs, and religion. The limitation of this study is the scope of the study which is still limited to the normative aspects of multicultural values. This study has not analyzed in depth the psychological dynamics of students or the institutional structure that influences the internalization of these values. The originality of this study lies in its approach that integrates Islamic educational values ​​with the concept of multiculturalism in inclusive formal education practices. This study also highlights the interaction between students and teachers from various religious backgrounds directly in the context of religious learning, which is rarely explored in previous studies.